Peran Kepemimpinan Transformasional dalam Pengembangan Sumber Daya Manusia pada Organisasi Pemerintahan: Sebuah Studi Kualitatif Deskriptif - Muh. Zhafri (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2026)
This research aims to analyze in depth the role of transformational leadership in human resource development in a local government organization. This study uses a descriptive qualitative approach with data collection techniques through in-depth interviews, participatory observation, and documentation. The research informants include structural leaders, functional officers, and HR development staff. Data analysis was carried out using the Miles and Huberman model which includes data reduction, data presentation, and conclusion drawn. The results show that leaders with transformational characteristics play a significant role in creating a competitive work culture, increasing employee readiness to face change, and strengthening motivation and innovation in HR development programs. The dimensions of idealized influence, inspirational motivation, intellectual stimulation, and individualized consideration have been proven to encourage the improvement of employee competence, especially in the field of digitization of administration and public service innovation. However, the effectiveness of transformational leadership in human resource development is still influenced by structural constraints in the form of bureaucratic hierarchy, budget limitations, and resistance to change from some senior employees. This research emphasizes that the transformation of government organizations requires a leadership style that is able to build a learning culture, manage change, and strengthen the capacity of the apparatus in the long term. This study provides theoretical and practical implications for strengthening human resource management and bureaucratic reform in Indonesia.